Filsafat Hukum Islam dan Hikmah - Derta Nur Anita; Sarbini Sarbini; M. Bahtiar Ubaidillah (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Philosophy of Islamic law is the knowledge of the nature, secret, and the goal of Islam both concerning the material and the process of its adoption. Philosophy of Islamic law will make Islamic law can adapt to the conditions and needs of its day. hikmah means wisdom or deep meaning. Wisdom also means knowing the superiority of something through knowledge. Tasawuf experts interpret wisdom as knowledge of God's secrets in creating something. Scientists of Islamic law define wisdom as a motivation in law reconciliation to achieve kemaslahatan and reject kemudharatan. Philosophy of Islamic law and hikmah have similiaritis in function and purpose, even most Muslim philosophers consider wisdom to be a synonym of philosophy.